Learning Progression of Students’ Reasoning about Life Cycles - Hayat Hokayem; Ihsan Ghazal; Savannah R. Graham (Science Education International, 2023)
This study explored elementary students’ reasoning about the life cycles of various organisms, including insects and amphibians. The study took place in a private school in Lebanon with 24 fifth-grade students. Students participated in a life cycle unit with pre and post-written assessments about what they learned and interviews to help determine their reasoning about life cycles. Using our findings, we suggest a learning progression (LP) approach to guide students over time in their learning about life cycles and their importance for species persistence within an ecosystem. Two LPs were developed from this study: Reasoning about the cyclic nature of life and comparison of life cycle stages. Overall, students improved their understanding of the cyclical nature of life, but comparing organisms’ structures, stages, and life cycles proved to be more challenging. These LPs have direct implications for elementary instruction about life cycles, organisms, and species.